Surgical extraction of an unusual macrocystic lymphatic malformation in the buttock: case report - Francisco Antonio Rodríguez-García; Cuauhtly Gallegos-Sierra; José Luis Villarreal-Salgado; Karla Jimenez-Pavon; Karen Morfin-Meza; Joel Ramos-Maciel; Diego Armando Fierro-Rodríguez; Enrique Romero-Algara; Pablo Bonilla-Catalán; Emmanuel Dorado-Hernández; Quitzia Libertad Torres-Salazar (SpringerOpen, 2021)
Abstract Background Macrocystic lymphatic malformation is a rare benign skin disorder, especially the anogenital area, which covers less than .5% of the reported cases. It can cause vesicular and papular lesions on the face, trunk, extremities, and, less frequently, anogenital areas. Although there are currently several therapeutic options, surgical excision is the most widely used, considering the lowest recurrence rate. Case presentation In this article, we describe the case of a 15-year-old male patient who presented with herpetiform skin lesions, corresponding to the diagnosis of macrocystic lymphatic malformation, in the lower region of the right buttock. After confirmation of the diagnosis by histopathology, surgical excision was performed with a tensor fascia lata graft, with successful aesthetic and functional results. Conclusions Considering the diagnosis of macrocystic lymphatic malformation is of utmost importance, although its presence is unusual, to differentiate it from other herpetiform lesions. Despite the existence of multiple approaches today, definitive treatment with surgical extraction is necessary, both to improve the cosmetic aspect and to prevent associated complications. It is suggested that histopathological and imaging diagnostic tools be used as a routine element, in order to increase therapeutic success, as well as decrease the risk of recurrences. Evidence-based medicine ranking Level IV